Overcoming establishment thresholds for peat mosses in human‐made bog pools. Issue 6 (30th May 2021) - Temmink, Ralph J. M.; Cruijsen, Peter M. J. M.; Smolders, Alfons J. P.; Bouma, Tjeerd J.; Fivash, Gregory S.; Lengkeek, Wouter; Didderen, Karin; Lamers, Leon P. M.; van der Heide, Tjisse
Abstract: Globally, peatlands have been affected by drainage and peat extraction, with adverse effects on their functioning and services. To restore peat‐forming vegetation, drained bogs are being rewetted on a large scale. Although this practice results in higher groundwater levels, unfortunately it often creates deep lakes in parts where peat was extracted to greater depths than the surroundings. Revegetation of these deeper waters by peat mosses appears to be challenging due to strong abiotic feedbacks that keep these systems in an undesired bare state. In this study, we theoretically explore if a floating peat mat and an open human‐made bog lake can be considered two alternative stable states using a simple model, and experimentally test in the field whether stable states are present, and whether a state shift can be accomplished using floating biodegradable structures that mimic buoyant peat. We transplanted two peat moss species into these structures (pioneer sp. Sphagnum cuspidatum and later‐successional sp. S. palustre ) with and without additional organic substrate. Our model suggests that these open human‐made bog lakes and floating peat mats can indeed be regarded as alternative stable states. Natural recovery by spontaneous peat moss growth, i.e., a state shift from open water to floating mats, is only possible when the water table is sufficiently shallow to avoid light limitation (<0.29 m at our site). Our experiment revealed that alternative stable states are present and that the floating structures facilitated the growth of pioneer S. cuspidatum and vascular plants. Organic substrate addition particularly facilitated vascular plant growth, which correlated to higher moss height. The structures remained too wet for the late‐successional species S. palustre . We conclude that open water and floating peat mats in human‐made bog lakes can be considered two alternative stable states, and that temporary floating establishment structures can induce a state shift from the open water state to peat‐forming vegetation state. These findings imply that for successful restoration, there is a clear water depth threshold to enable peat moss growth and there is no need for addition of large amounts of donor‐peat substrate. Correct species selection for restoration is crucial for success.